ROLE OF MATRIX METALLOPROTEINASES (MMPS) IN COLORECTAL CANCER (CRC): REGULATION AND THERAPEUTIC INTERVENTIONS - SUDIP DAS, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
The matrix metalloproteinases (MMPs) comprises of proteases that are well regulated with their endogenous anti-proteinases in many physiological processes with the right expression and stoichiometry. The dysregulation of that metalloproteinases and anti-proteinases play important role in several pathological processes and more viciously in tumour progression and the metastasis. It has been shown by investigators that matrix metalloproteinases (MMPs) play important role in colorectal cancer (CRC) invasion and metastasis. The MMPs able to degrade and/or activate proteins, that play crucial role in tumour initiation, progression and metastases, suggesting that proper regulation and/or management of MMPs during colorectal cancer would be the possible diagnostic, prognostic and therapeutic targets of patients of CRC. Therefore, MMPs have been unanimously considered as the advanced and one of the therapeutic strategies focusing on mainly down regulating or blocking these proteinases by several natural as well as synthetic inhibitors. In fact, many clinical trials by researchers using MMP inhibitors were going on to manage this disease by so many different and efficient ways. Based on this evidence, the pharmaceutical industry produced several well tolerated, active MMP inhibitors (MMPIs) which demonstrated efficacy in different CRC models too.